FAKTOR YANG MEMENGARUHI KEJADIAN EPILEPSI PASCASTROKE DI RSUP DR HASAN SADIKIN - Indra Gunawan Affandi,* Suryani Gunadharma,* Anam Ong* (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION STROKE IS THE MOST COMMONLY IDENTIFIED CAUSE OF EPILEPSY IN ADULT STROKE PATIENTS WITH CORTICAL INVOLVEMENT HEMORRHAGIC STROKE SEVERE NEUROLOGICAL DEFICITS AND OLD AGE ARE FACTORS WHICH INFLUENCE THE INCIDENCE OF POSTSTROKE EPILEPSY